2008
DOI: 10.1029/2007gl033000
|View full text |Cite
|
Sign up to set email alerts
|

Positive leader characteristics from high‐speed video observations

Abstract: [1] Based on analyses of high-speed video recordings of cloud-to-ground lightning in Brazil and the USA, the characteristics of positive cloud-to-ground (+CG) leaders are presented. The high frame rates permitted the average, 2-dimensional speeds of development along the paths of the channels to be resolved with good accuracy. The values range from 0.3 to 6.0 Â 10 5 ms À1 with a mean of 2.7 Â 10 5 ms À1. Contrary to what is usually assumed, downward +CG leader speeds are similar to downward ÀCG leader speeds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
125
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(137 citation statements)
references
References 15 publications
12
125
0
Order By: Relevance
“…One observational feature that supports the aforementioned mechanism is that GJs emerge from thundercloud tops with speeds on the order of or less than the lower limit of streamer speeds, which is 10 5 m/s [Bazelyan and Raizer, 2000, p. 39] but consistent with speeds of laboratory and lightning leaders [Bazelyan and Raizer, 1998, Section 6.2]. For instance, Briels et al [2008] have measured laboratory streamer speeds in the range 1-40 10 5 m/s, while Andreev et al [2008] and Saba et al [2008] have measured speeds in the range 1-5 10 4 m/s and 3-60 10 4 m/s, for laboratory and lightning leaders, respectively. Modeling results of leader speeds at reduced air densities reiterate this assertion Pasko, 2012, 2013].…”
Section: Gigantic Jet Acceleration As Evidence Of Its Vertical Structmentioning
confidence: 99%
“…One observational feature that supports the aforementioned mechanism is that GJs emerge from thundercloud tops with speeds on the order of or less than the lower limit of streamer speeds, which is 10 5 m/s [Bazelyan and Raizer, 2000, p. 39] but consistent with speeds of laboratory and lightning leaders [Bazelyan and Raizer, 1998, Section 6.2]. For instance, Briels et al [2008] have measured laboratory streamer speeds in the range 1-40 10 5 m/s, while Andreev et al [2008] and Saba et al [2008] have measured speeds in the range 1-5 10 4 m/s and 3-60 10 4 m/s, for laboratory and lightning leaders, respectively. Modeling results of leader speeds at reduced air densities reiterate this assertion Pasko, 2012, 2013].…”
Section: Gigantic Jet Acceleration As Evidence Of Its Vertical Structmentioning
confidence: 99%
“…The first type corresponds to the ordinary +CG [27] Of all the positive CGs in our data set, 118 (63.78%) of the positive CG flashes were ordinary positive CG flash, 39 (21.08%) exhibited IC discharge only after the strokes, 10 (5.41%) exhibited IC discharge only before the strokes, and 18 (9.73%) had IC discharge both before and after the strokes (see Table 5). If the IC discharge was recorded during the 200 ms pre-trigger time and no obvious preliminary breakdown and leader processes can be identified, we attribute this kind of positive CG flashes to be initiated by intracloud discharges, as found by Kong et al [2008] and Saba et al [2008] using high-speed video observations. The preliminary breakdown and leader processes are not considered as intracloud discharge in our analysis.…”
Section: Morphologies Of Positive Cg Flashes Accompanied By Ic Dischargementioning
confidence: 99%
“…However, there are also reports of much faster positive leaders. For example, Saba et al [2008] observed speeds of downward positive leaders in the range of 0.3 to 6 · 10 5 m s À1 with a mean of 2.7 · 10 5 m s À1 . Biagi et al [2011] recorded a similar speed in an upward leader, up to 2.1 · 10 5 m s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Observed with high-speed cameras, they look like luminous streaks occurring 3000-5000 times per second [Montanyà et al, 2012], revealing the locations of barely visible positive leader branches [Saba et al, 2008]. Their speed (>4 · 10 6 m s À1 ) [e.g., Saba et al, 2008] is rarely resolved by present VHF time-of-arrival systems, but they are detectable and often used to identify negative charge layers [Rust et al, 2005].…”
Section: Introductionmentioning
confidence: 99%